2018
DOI: 10.3389/fphar.2018.00975
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Use of Strontium Ranelate Reduces the Progression of Experimental Osteoarthritis

Abstract: Introduction: Strontium ranelate (SrRan) has the potential to interfere in the progression of osteoarthritis (OA), multifactorial disease associated with mechanical problems and articular inflammatory changes.Objectives: This study aimed to test the effects of prophylactic and therapeutic use of SrRan on clinical parameters of pain, the inflammatory process, and degradation of the articular cartilage.Methods: This was an experimental study, using a model of knee OA induced by intra-articular injection of monoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…98 There are other antiresorptive agents (such as OPG, cathepsin K (CTSK) inhibitors and strontium ranelate) that may exert protective effects on subchondral bone and cartilage in animal models and serve as disease-modifying OA drugs for clinical treatment of OA. [99][100][101] Intriguingly, calcitonin, which is known for targeting subchondral bone remodelling, also leads to intracellular cAMP accumulation and then promotes chondrocyte anabolism by binding to its receptors on human OA chondrocytes. 102 Two phase III trials have reported a beneficial effect of bioactive oral calcitonin on joint pain and biochemical indicators of bone and cartilage degradation in patients with OA.…”
Section: Targeting the Subchondrol Bone Microenvironment For The Treamentioning
confidence: 99%
“…98 There are other antiresorptive agents (such as OPG, cathepsin K (CTSK) inhibitors and strontium ranelate) that may exert protective effects on subchondral bone and cartilage in animal models and serve as disease-modifying OA drugs for clinical treatment of OA. [99][100][101] Intriguingly, calcitonin, which is known for targeting subchondral bone remodelling, also leads to intracellular cAMP accumulation and then promotes chondrocyte anabolism by binding to its receptors on human OA chondrocytes. 102 Two phase III trials have reported a beneficial effect of bioactive oral calcitonin on joint pain and biochemical indicators of bone and cartilage degradation in patients with OA.…”
Section: Targeting the Subchondrol Bone Microenvironment For The Treamentioning
confidence: 99%
“…Strontium ranelate, an old antiosporotic drug, [1,2] remains of great interest in bone healing, [3][4][5][6] dentistry [7][8][9] and several biological applications. [10][11][12][13][14][15][16] Despite its low toxicity, the drug was discontinued by the producer after the European Medicines Agency reported a slight increase (from 1.1 to 1.7% ) in cardiovascular events involving 7000 tested patients who used placebo or strontium ranelate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A histopathological analysis of the synovial membrane and articular cartilage showed encouraging results, suggesting the possible efficacy of S. dulcis in the treatment of OA at the dose tested. Hyaline cartilage is the most relevant articular tissue in the pathogenesis of this disease [6]. Although OA is characterized by subchondral bone sclerosis, it is uncertain that bone changes are the cause or consequence of the lesions, given that the cartilage properties depend on the bone bed, which can be affected by the mechanical function of the cartilage [53].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a chronic, complex disease characterized by loss, alteration and progressive degeneration of cartilage and subchondral bone; reduction of joint space; synovitis; pain, and formation of osteophytes [1,2]. OA mainly affects the joints that are given greater weight, such as the knees, [3] It alters an individual’s the quality of life [4,5], is the most frequent cause of musculoskeletal disease and pain [6,7], and impacts daily living and work activities [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation